Adrenergic receptor polymorphisms and platelet reactivity after treatment with dual antiplatelet therapy with aspirin and clopidogrel in acute coronary syndrome - Cuisset, Thomas; Hamilos, Michalis; Delrue, Leen; Frere, Corinne; Verhamme, Katia; Bartunek, Jozef; Saut, Noemie; Bonnet, Jean Louis; Eijgelsheim, Mark; Wijns, William; Alessi, Marie-Christine; Barbato, Emanuele (Thrombosis and Haemostasis, 2010)
Platelet response to clopidogrel shows inter-individual variability that is partially explained by genetic polymorphisms. This variability affects clinical outcome when clopidogrel is administered in patients with acute coronary syndrome (ACS). Catecholamines, released during ACS, contribute to platelet aggregation through platelet α2A- (α2A-AR) and β2-adrenergic receptor (β2-AR) stimulation. It was the objective of this study to assess the potential influence of α2A-AR and β2-AR gene polymorphisms on platelet reactivity after dual antiplatelet therapy with aspirin and clopidogrel in ACS. We screened 641 ACS patients for 6.3/6.7 kb α2A-AR polymorphism, and for Arg16Gly and Gln27Glu β2-AR polymorphism. After 600 mg clopidogrel, we assessed ADP 10 μmol-induced platelet aggregation (ADP-Ag) and vasoactive stimulated phosphoprotein (VASP). All single nucleotide polymorphisms were in Hardy-Weinberg equilibrium. A slight though negligible association was found between 6.3 kb allele of α2A-AR with platelet reactivity ADPAg induced (beta: –2.91 [-5.68;-0.14], p=0.04). A borderline not significant reduction in PRI VASP was observed in 6.3 kb α2A-AR carriers (beta: –3.81 [-0.09;7.72], p=0.06). No significant effect on platelet parameters was observed for the other tested polymorphisms. Common α2A- and β2-adrenergic receptor polymorphisms do not show any major impact on residual platelet reactivity in non-ST-elevation ACS when a dual antiplatelet therapy with 250 mg aspirin and 600 mg clopidogrel is administered.
Keywords: Antiplatelet agents; coronary syndrome; single nucleotide polymorphisms